PHRASEOLOGICAL REPRESENTATION OF THE CONCEPT “CONSCIENCE” IN MODERN ENGLISH: A COGNITIVE, AXIOLOGICAL AND LINGUOCULTURAL ANALYSIS (International journal of artificial intelligence, 2026)
The article provides an in-depth cognitive-semantic and axiological analysis of the phraseological representation of the concept “conscience” in modern English. The research is grounded in contemporary cognitive linguistics, conceptual metaphor theory, and phraseological studies. The study examines how phraseological units serve as a primary linguistic mechanism for verbalizing moral cognition, ethical self-regulation, and evaluative judgment. Drawing on British and American English material, the paper identifies the internal structure of the concept, including its semantic core, near and far periphery, and dominant metaphorical models. Special attention is paid to the interaction between linguistic meaning, cultural values, and moral norms encoded in phraseology. The results demonstrate that phraseological units not only reflect individual moral experience but also function as carriers of collective ethical knowledge, thus playing a crucial role in shaping the English linguistic worldview.